Síntese e caracterização de argila organofílica: estudo da influência do pH na adsorção de cromo visando o tratamento de rejeitos de curtumes - Emilio Gomes Domingues Neto (2019)
The growing rigidity of environmental legislation, coupled with the impacts of inadequate tailings disposal, has challenged several industries to seek more efficient ways to treat their tailings. The leather manufacturing industry is constantly growing, bringing with it a great deal of waste. One of the most generated solid residues in this type of industry is the so-called "debris powder". This residue is generated in the finishing stage of the leather, where it is scraped to the desired thickness by the consumer. These chips are generated in large amounts per day, have a high concentration of heavy metals in their composition (mainly chromium, have low specific gravity, are difficult to compaction and are usually destined to industrial landfills. the adsorption of contaminants using organophilic clay as adsorbent has gained space as a new and potentially viable technology, mainly due to the simplicity of operation and gains in the removal of the contaminant. clay and then organophilization so that it can be applied in a solution of potassium dichromate, aiming at the removal of Cr (VI), the main contaminant present in tannery residues.The results of the analyzes carried out showed evidence that the organofiliza of the clay occurred, either by increasing basal distance or by the results obtained in the chemical analysis. The results indicated good efficiency in the removal of chromium, especially for a pH equal to 2, where the removal was the maximum obtained.